2018
DOI: 10.1177/1724600817748538
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of CD56 immunohistochemistry in thyroid lesions

Abstract: Collectively, these results indicate that the rate of loss of CD56 immunohistochemistry expression was significantly higher in malignant tumors, such as papillary thyroid carcinoma and follicular carcinoma, than in follicular adenoma, benign follicular nodule, and Hashimoto's thyroiditis. As such, CD56 immunohistochemistry can be useful in differentiating follicular variant papillary thyroid carcinoma from follicular adenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 18 publications
3
22
0
Order By: Relevance
“…Neoplasms of neuroendocrine or hematopoietic origins over‐produce NCAM, as do brain tumours (Jensen & Berthold, 2007; Zecchini & Cavallaro, 2010). Conversely, in pancreatic (Fogar et al, 1997), colorectal (Roesler, Srivatsan, Moatamed, Peters, & Livingston, 1997) astrocytic (Sasaki et al, 1998) and thyroid (Muthusamy et al, 2018; Pyo, Kim, & Yang, 2018) cancer, low levels of NCAM have been correlated with increased malignancy. In prostate cancer, however, the role of NCAM has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Neoplasms of neuroendocrine or hematopoietic origins over‐produce NCAM, as do brain tumours (Jensen & Berthold, 2007; Zecchini & Cavallaro, 2010). Conversely, in pancreatic (Fogar et al, 1997), colorectal (Roesler, Srivatsan, Moatamed, Peters, & Livingston, 1997) astrocytic (Sasaki et al, 1998) and thyroid (Muthusamy et al, 2018; Pyo, Kim, & Yang, 2018) cancer, low levels of NCAM have been correlated with increased malignancy. In prostate cancer, however, the role of NCAM has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Hector Battifora Mesothelial Cell-1 (HBME-1), Galectin-3 and Cytokeratin-19 (CK19) have been the most frequently used antibodies in thyroid pathology, although a wide range of sensibility and specificity values of these markers has been reported 3,6,[11][12][13][14][15] . The rates of loss of CD56 IHC expression were significantly higher in malignant thyroid tumors, such as papillary thyroid carcinoma and follicular carcinoma than in FA and other benign lesions, such as follicular adenoma, benign follicular nodule, and Hashimoto's thyroiditis 16 .…”
Section: Introductionmentioning
confidence: 86%
“…CD56 is a neural cell adhesion molecule and is characteristically expressed in normal thyroid follicular cells and benign thyroid nodules but not in PTC [7][8][9][10]. That CD56 works well as a diagnostic marker for PTC against benign thyroid lesions has been shown in several previous studies [11][12][13]. However, little is known about the CD56 expression in NIFTP and the uncommon variants of PTC, such as the tall cell variant.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have shown that follicular variant PTC (FVPTC) has reduced expression of CD56 expression compared to benign thyroid nodules, suggesting the utility of CD56 immunostaining for the differential diagnosis [14]. Although most authors agree that CD56 expression is reduced in the process of thyroid carcinogenesis [14][15][16][17], there is still a lack of data about the CD56 expression in different variants of PTC other than classic PTC or about the utility of CD56 as a diagnostic marker in rare PTC variants [13].…”
Section: Introductionmentioning
confidence: 99%